Enhancing collaborative clinical reasoning among multidisciplinary healthcare teams in a neurosurgery ICU: insights from video-reflexive ethnography - Ching-Yi Lee; Ching-Hsin Lee; Sze-Yuen Yau; Hung-Yi Lai; Po-Jui Chen; Mi-Mi Chen (BMC Medical Education)
Abstract Background Clinical reasoning is a critical skill for healthcare professionals, vital for making accurate diagnoses and effective treatment decisions. This study focuses on enhancing collaborative clinical reasoning (CCR) among multidisciplinary healthcare teams in a neurosurgery intensive care unit (NICU) in Taiwan. The study utilizes video-reflexive ethnography (VRE) to examine the factors influencing CCR, the cognitive processes involved, and the efficacy of VRE in promoting CCR. Methods The study employed a qualitative research design, utilizing VRE. Participants included 17 healthcare professionals from a NICU, comprising attending physicians, residents, nurses, and respiratory therapists. Data collection involved video recordings of daily ward rounds, field observations, and reflexive interviews where participants reviewed video clips of their interactions. Thematic analysis was conducted on the transcripts of video recordings and interview. Results Thematic analysis revealed seven key themes in CCR: information sharing, active verbal and behavioral information gathering, information processing and recall, modification and discussion, short-term indications, and management plans and goals. Information sharing was fundamental, with team members frequently exchanging patient data to ensure a common understanding. Active information gathering, both verbal and behavioral, was crucial for obtaining real-time patient insights. Cognitive processing involved synthesizing data to form initial hypotheses, while modification and discussion highlighted the iterative nature of CCR. Conclusions This study underscores the importance of effective communication, active information gathering, and iterative discussions in enhancing CCR. VRE proved to be a valuable tool for promoting self-awareness and continuous improvement among healthcare teams. The findings suggest that education programs should focus on developing teamwork and communication skills, and interventions should aim to optimize information flow and foster a culture of open communication. By enhancing CCR, healthcare teams can improve patient outcomes and ensure safer healthcare delivery. Clinical trial number Not required, as this is not a clinical trial and does not involve any healthcare interventions with human participants.